The Effect of Lecturer Service Quality on Students' Satisfaction in Private Universities - Patras, Yuyun Elizabeth; Hidayat, Rais (Jurnal Manajemen, 2020)
One of the roles of the university is to support national education goals as part of educating students. Student satisfaction is an important variable for the existence and sustainability of a university, especially a private universities.This research aims to analyze the effect of lecturer service quality on student satisfaction.This research uses quantitative research with survey methods. The population of this research were students of a private university at Universitas Pakuan with 543 respondents. The findings of this research were that there was a positive and significant influence between the lecturer service quality on student satisfaction. This means that efforts to increase student satisfaction can be done by improving the quality of lecturer services. Meanwhile, from the 5 dimensions of lecturer service quality, it was found that the empathy dimension had the greatest influence compared to other dimensions of lecturer service quality.